Glutathione promotes aluminum tolerance in rice through cell wall remodeling and nitrogen metabolic regulation - Muhammad Riaz; Saddam Hussain; Qurban Ali; Lei Yan (Ecotoxicology and Environmental Safety)
Aluminum (Al) toxicity is a major constraint for plant growthand productivity, particularly in acid soils, in which toxic Al3+ ions are more soluble and available. Glutathione (GSH), a nonprotein thiol tripeptide widely recognized as a pivotalmolecule in detoxifying endogenous/exogenous compounds and redox homeostasis, has been proven to ameliorate multiple abiotic stresses. However, the mechanisms involved in the GSH-induced alleviation of Altoxicity in rice seedlings are poorly understood. In this work, we fill this knowledge gap by conducting a thorough study of the possible ameliorative effects of exogenous GSH on rice seedlings subjected to Al stress, with a specific focus on exploring the potential effects of exogenous GSH on Al distribution, pectin modification, antioxidant defense, and nitrogen metabolism. The experiment consisted of four treatments: CK (control), GSH (50 µM GSH), Al (100 µM AlCl3), and GSH+Al (50 µM GSH+100 µM AlCl3). In our results, decreased root and shoot lengths, chlorophyll contents, and activity and contents on nitrogen metabolism-related enzymes were exhibited under Al toxicity. In contrast, GSH treatment remarkably reduced Al contents in rice root and shoot, and reduced lipid peroxidation compared to Al treatment alone. Particularly, GSH+Al treatment inhibited Al accumulation in root tips by 53.73 % and in cell wall (CW) by 34.61 %. Glutathione also inhibited pectin methylesterase (PME) activity by 50.15 %, resulting in a 58.05 % increase in pectin methylation. Ammonium (NH4+) contents were decreased by 4.3 % (P < 0.05), and nitrate (NO3-) contents were increased by 10.97 % (P < 0.05) in GSH+Al treated leaves compared to Al treatment only. Glutathione enhanced the citric acid concentration and improved the activities of key enzymes associated with nitrogen metabolism. Therefore, exogenous GSH may decrease Al toxicity in rice seedlings by reducing oxidative stress and Al concentrations in different plant of rice plants.